Explaining moral knowledge - Leibowitz, Uri D. (Brill, 2014)
In this paper I assess the viability of a particularist explanation of moral knowledge. First, I consider two arguments by Sean McKeever and Michael Ridge that purport to show that a generalist, principle-based explanation of practical wisdom—understood as the ability to acquire moral knowledge in a wide range of situations—is superior to a particularist, non-principle-based account. I contend that both arguments are unsuccessful. Then, I propose a particularist-friendly explanation of knowledge of particular moral facts. I argue that when we are careful to keep separate the various explanatory tasks at hand we can see that a particularist-friendly explanation of the fact that (e.g.,) Jane knows that A is morally right might not be so difficult to come by. Moreover, I suggest that a particularist approach to explaining knowledge of particular moral facts may go some way towards discharging the challenge of moral scepticism.